Research and Application of the Composite Reservoir Stimulation Technology for Ultra-High-Temperature Ultra-Deep Naturally-Fractured Carbonate Reservoirs. Issue 1 (November 2020) - Duan, Guifu; He, Chunming; Liang, Chong; Cai, Bo; Yan, Jun; Wang, Chao
Abstract: The Ordovician buried-hill carbonate reservoir in the northern Jizhong Sag of China is seen with abundance in hydrocarbon resources. Nonetheless, attempts of multiple reservoir stimulation technologies have all failed to make breakthrough, due to its lithological complexity (mixture of dolomite and limestone), ultra-high temperatures (180°C) and high in-situ stress gradients (0.023 MPa/m), Given the aforementioned reservoir geological challenges, reservoir evaluation, technology optimization and plan design starting from the reservoir geological characteristics have been carried out, and the "composite" reservoir stimulation technology for ultra-high-temperature ultra-deep naturally-fractured carbonate reservoirs has been proposed. In terms of the short effective affected distance of acid under high temperatures (180°C), low conductivity sustainability owing to high closure stresses (induced by the burial depth of 5, 000 m), extreme difficulties in expanding stimulated reservoir volumes (large lateral in-situ stress differences and long vertical spans), the practice of "multi-stage injection, temporary plugging and diversion, and propped acid fracturing" highlighting high pump rates and combination of low- and high-viscosity fluids (acid and fracturing fluids) has been developed and evolves into the network fracturing technology capable of inter-layer temporary isolation and within-layer diversion. The above technology has been applied in Well AT1x, with high volumes of fluid consumption and the maximum pump rate of 11 m 3 /min. Safe and efficient operation over six hours featuring challenges such as 3, 000 m 3 of composite fluids, ultra-high temperatures and ultra-high pressures is achieved. On-site monitoring such as the micro-seismic monitoring and simulation results show that compared with the previous reservoir stimulation, the developed technology presents SRV 3.5 times larger, and results in three-dimensional reservoir reconstruction. The post-fracturing daily gas production amounts to 409, 000 m 3 and daily oil production, 71 m 3 . In production testing, the wellhead pressure maintained over 25 MPa, and the daily gas production exceeds 100, 000 m 3, which indicate stable pressures and production, and a safe wellbore. The application accomplishes the design goal of integrated exploration and exploitation, and geology and engineering, and provides references for reservoir simulation of analogous reservoirs.